Peran Teknologi Digital Dalam Perkembangan Dunia Perancangan Arsitektur - Andy Satria; Asri Mahara; Alwis Anasyon Situmorang; Arya Novandli (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The field of architecture has undergone rapid development within both academic and professional circles. Digital architecture, a concise term describing the use of communication and information technology in the entire planning and design process, has significantly influenced architectural education worldwide. It serves as a means to bridge the quality gap between architectural education in developed and developing countries. In Indonesia, digital architecture has been a subject of debate since its inception, garnering both proponents and opponents. Many still hold the belief that computers are merely new tools, akin to drawing instruments, for architects. However, the current progress reveals the availability of numerous computer modeling programs that support architectural design. These programs enable the visualization of building conditions before construction, becoming commonplace tools in consultancy firms and educational institutions, embraced by both lecturers and students. Consequently, the impact of information technology on the evolution of the architectural world is evident. The growing reliance on digital modeling programs in architectural design demonstrates a paradigm shift. This technological influence extends beyond individual buildings to encompass urban modeling, both in physical and non-physical aspects. Therefore, it is understood that the influence of information technology will continue to grow in the architectural realm, with digital programs playing a pivotal role in supporting the building design process.